Bite Mark Analysis with “Stamping” Method in Child Abuse Case: A Case Report - Dina Karimah Putri (Science and Technology Publications, Lda., 2018)
Bite marks as evidence of a crime cases are commonly found in cases such as sexual assault, struggle, homicide and child abuse. Bite marks are thought to help uncover the biter because human teeth are individualistic and have different shapes, sizes and patterns for each individual, even identical twins. This report is to explain how to analyze bite marks using a “stamping” method in child abuse cases. In this case report, we present a case of 17-month-old toddler who was found dead in his house with head trauma and two scars resembling human bite marks on the right chest and abdomen. Those scars appeared not as a new bite and that implies these bites happened before the death of the toddler. Investigators assumed that he was a victim of child abuse which led to the murder. Although the autopsy results showed the cause of death was not from the bite but from the blunt object trauma to his head, by analyzing the evidence of bite marks found on the victim's body it can be expected to pr ovide information about the motives and background of the murder and help find the perpetrator of the bite-related injury. Analysis was done by using a "stamping" method of the suspect’s bite marks who was asked to bite a wax that had been flexed with heat and then superimposed with a photo of bite marks on the victim's body with a size close to the actual size. The result showed that the bite marks matched the bite of the victim's father who was also suspected of being the murderer. The bite pattern of the toddler’s father had similarity with the bite marks found on the victim’s body, so he has possibility to be included as the suspected biter.